The End of Education? Nietzsche, Foucault, Genealogy - Allen, Ansgar (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
This paper considers the end of education and the demands it makes upon us. It argues that the feared end of education, underpins, and unduly shackles reflection on the current crisis of education. As a spectral, abysmal prospect, it both fetters and stimulates educational critique, mobilising critique to the support of a cause it cannot question because it is committed to its rescue. In a time of crisis, we find ourselves tied only more firmly to education, forced to express or enact our faith in educational redemption. Drawing from the work of Friedrich Nietzsche and Michel Foucault, a contrasting, genealogical critique of education is imagined, one that might defer the impulse of educational redemption and defy the limits on thought currently imposed. A genealogy of education is outlined that would strip education of its dignity, and thereby challenge its dominion. The necessary incoherence of such an approach is explored.